A Task for Sisyphus Why Europe's Roma Policies Fail - Rostas, Iulius (Central European University Press, 2019)
Despite the increasing number of policy measures and initiatives targeting the Roma in Europe, their position has continued to worsen, which requires answers from policymakers, activists and academics. The author sums up why Roma policies fail on European and national levels as follows: failure to define the target group; to provide good information and data; to establish a mechanism for effective participation of Roma; to allow adequate debate and consultation; to define the problems and to frame the issue; to coordinate between central and local level; to design policies without monitoring and evaluation; and finally failure of regulative framework. Each of the above is expounded in the book with a number of recommendations. These include conceiving the Roma as a "politically insular minority," giving greater consideration to the specificities of Romani ethnic identity and setting up mechanisms that ensure that the voice of Roma is heard during the decision-making processes.